1998
DOI: 10.1038/sj.onc.1201653
|View full text |Cite
|
Sign up to set email alerts
|

Ha-ras and N-ras regulate MAPK activity by distinct mechanisms in vivo

Abstract: The Ras GTPases function as molecular switches, regulating a multiplicity of biological events. However the contribution, if any, of a speci®c c-Ras isoform (Ha-, N-, or Ki-ras A or B) in the regulation of a given biological or biochemical process, is unknown. Murine C3H10T1/2 ®broblasts transformed with activated (G12V)Ha-ras or (Q61K)N-ras proliferate in serum-free media and have constitutive MAPK activity. The growth factor antagonist, suramin, inhibited the serum-independent proliferation of Ha-ras transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 31 publications
(53 reference statements)
5
59
1
Order By: Relevance
“…Biochemical analysis revealed that Raf-1 failed to interact with the activated Ha-Ras protein in the V12H10 cells, but instead, Raf-1 was found to be associated with the wild-type endogenous c-N-Ras protein. Suramin treatment disrupted the c-NRas⅐Raf-1 complex in V12H10 cells but did not disrupt the N-Ras⅐Raf-1 complex detected in the N-Ras-transformed K61N10 cells (15). The failure of oncogenic Ha-Ras to associate with Raf-1 is contrary to current dogma, which suggests that it is the direct association of an oncogenic Ras with Raf-1 that is responsible for regulating the MAPK cascade.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Biochemical analysis revealed that Raf-1 failed to interact with the activated Ha-Ras protein in the V12H10 cells, but instead, Raf-1 was found to be associated with the wild-type endogenous c-N-Ras protein. Suramin treatment disrupted the c-NRas⅐Raf-1 complex in V12H10 cells but did not disrupt the N-Ras⅐Raf-1 complex detected in the N-Ras-transformed K61N10 cells (15). The failure of oncogenic Ha-Ras to associate with Raf-1 is contrary to current dogma, which suggests that it is the direct association of an oncogenic Ras with Raf-1 that is responsible for regulating the MAPK cascade.…”
contrasting
confidence: 52%
“…Cell Culture and Transfections-V12H10 and K61N10 fibroblasts are derived from normal mouse C3H10T1/2 fibroblasts by transfection with activated (G12V)Ha-Ras and (Q61K)N-Ras constructs, respectively and are described elsewhere (15). All cell lines were maintained in DMEM ϩ fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been obtained using indirect antagonism of Ras with HMG-CoA Reductase inhibitors and prenylation inhibitors, which reduce the C terminal prenylation required for Ras function. Although the specific function of each of the Ras isoforms is not known, different Ras isoforms have been shown to differ in their ability to activate certain effectors (21,22), and it may be that the different isoforms of Ras play distinct roles in control of proliferation acting via different downstream cascades.…”
Section: Discussionmentioning
confidence: 99%
“…1). It has been recognized that activation of different Ras isoforms results in distinct signaling outputs (9,14,15,(35)(36)(37), and the membrane microdomains such as rafts and caveolae most likely contribute to the segregated signaling (11,12). It should be noted that in some cell lines established from nonneural tissues H-Ras operates in membrane rafts, whereas K-Ras seems to be located outside rafts (13,38), in contrast with the selective enrichment of K-Ras in the rafts of the rat brain membranes (Fig.…”
Section: Fig 3 Gdp and Gtp␥s Inhibit Binding Of K-ras To Scop Lrrmentioning
confidence: 99%